Application Of Rectangular Matrices: Affine Cipher Using Asymmetric Keys - Maxrizal, Maxrizal; Aniska Prayanti, Baiq Desy (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2019)
In cryptography, we know the symmetric key algorithms and asymmetric key algorithms. We know that the asymmetric key algorithm is more secure than the symmetric key algorithm. Affine Cipher uses a symmetric key algorithm. In this paper, we introduce the Affine Cipher using asymmetric keys. Asymmetrical keys are formed from rectangular matrices.